2016
DOI: 10.1111/vec.12451
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion practice in dogs and cats: an Internet‐based survey

Abstract: Although some transfusion practices including the method and length of storage of blood products, use and screening of blood donors, and administration methods varied between VTH and PRH, most transfusion practices were similar. The information reported from this survey could aid the development of future veterinary transfusion consensus statements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 44 publications
(103 reference statements)
0
40
1
1
Order By: Relevance
“…Thus, staff at many veterinary hospitals perform crossmatches in dogs only 3 to 5 days after the first transfusion or in those with an unknown transfusion history, but do not test routinely before the first transfusion. 16 In 1913, Ottenberg et al 17 first demonstrated what was likely naturally occurring isoagglutinins and hemolysins in dogs. They described the agglutination and hemolysis to be weaker than that typically found in rats, rabbits, and people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, staff at many veterinary hospitals perform crossmatches in dogs only 3 to 5 days after the first transfusion or in those with an unknown transfusion history, but do not test routinely before the first transfusion. 16 In 1913, Ottenberg et al 17 first demonstrated what was likely naturally occurring isoagglutinins and hemolysins in dogs. They described the agglutination and hemolysis to be weaker than that typically found in rats, rabbits, and people.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In fact, the results of an online survey of participants from 73 veterinary referral or teaching hospitals indicate that only 11 of 73 (15%) performed a crossmatch evaluation for all dogs prior to transfusion. 16 Results from that study 16 suggest that veterinarians in most clinics do not routinely perform this evaluation for dogs that have not previously undergone a transfusion (ie, naïve recipients), although 72 of 73 (99%) respondents reported that they perform a crossmatch 3 to 5 days after the first transfusion has been given to a dog.…”
mentioning
confidence: 99%
“…In clinical veterinary medicine, plasma has traditionally been thawed using either controlled temperature WWBs or unregulated running warm water. A recent veterinary referral practice survey showed that the majority of blood products are warmed using WWBs while a few hospitals use commercial heating devices (Jagodich & Holowaychuk 2016). To our knowledge, there are no published guidelines for thawing FFP in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A terapia transfusional veterinária consiste na transfusão de sangue total ou hemocomponentes de um doador para um receptor, sendo indicada para cães em casos como sangramentos agudos, com o intuito de reparar a oxigenação, prevenir sangramentos e reestabalecer a homeostase; hematócrito muito baixo (menor ou igual a 15%); hemoglobina menor ou igual a 4g/ml; perda de mais de 30% do volume de sangue total; hipovolemia entre outros fatores que lançam a necessidade de uma transfusão sanguínea (HANN et al, 2014;HOHENHAUS, 2004;JAGODICH;HOLO-WAYCHUK, 2016).…”
Section: Terapia Transfusional E a Importância Da Determinação Dos Anunclassified